GLOBECOM 2009 - 2009 IEEE Global Telecommunications Conference 2009
DOI: 10.1109/glocom.2009.5426078
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Feedback Errors in Markov Models for SR ARQ Packet Delays

Abstract: Modern communication systems require effective error control techniques for wireless links. This problem is still relevant in many applications involving recently developed IEEE standards such as 802.16, or sensors for environmental monitoring in extreme conditions. A notable example is also underwater communication with acoustic transmission, where long delays may be present. Usually, such studies assume the availability of an error-free feedback channels which is used to perform retransmission requests in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…These are very common assumptions for the sake of clarity and they do not change the analysis substantially [10]. Further, we assume that the link layer is fully reliable, that is, every packet is transmitted (and retransmitted if needed) until it is received correctly.…”
Section: Sr Arq Queueing Model and Markov Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…These are very common assumptions for the sake of clarity and they do not change the analysis substantially [10]. Further, we assume that the link layer is fully reliable, that is, every packet is transmitted (and retransmitted if needed) until it is received correctly.…”
Section: Sr Arq Queueing Model and Markov Processesmentioning
confidence: 99%
“…Another related contribution is presented in [2], where the accurate approximation of packet delay statistics is discussed. In [10], SR ARQ was investigated in the presence of feedback errors, and it was discussed how this affects the packet delays.…”
Section: Introductionmentioning
confidence: 99%
“…Generative models are very efficient as they decrease the computation burden of real or simulation systems and subsequently they significantly reduce the simulation time. The main application of error models is to assess the performance and assist in the design of error control schemes and also the design of high layer wireless communication protocols [5]- [9]. Error models can characterize erroneous bit or packet sequences [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…We thus adopt SR, NACK-only based retransmission scheme in this general architecture of EEC for real-time multicast services. Additionally, many recent studies have shown that the Gilbert-Elliott (GE) model is a very good approximation for the packet loss model in a wireless channel [9]. Therefore, we will evaluate the throughput performance of the architecture using GE channel model in this paper.…”
Section: The General Architecture Of Eecmentioning
confidence: 99%
“…In this paper, for those parameterizations that include retransmissions, rather than focusing on a particular transport protocol, we consider a generic retransmission based scheme with the following feature: A Selective Repetition (SR), Negative-Acknowledgment (NACK)-only retransmission scheme is used. Actually, most real-time multicast transport protocols suggested to use a SR scheme rather than Go-Back-N due to its efficiency [9][10] [11]. We thus adopt SR, NACK-only based retransmission scheme in this general architecture of EEC for real-time multicast services.…”
Section: The General Architecture Of Eecmentioning
confidence: 99%